A community-based study on menopausal symptoms and quality of life in postmenopausal women in a rural area of West Bengal - Mohanta, Munu; Dwivedi, Malvika; Mukherjee, Mahul; Roy, Sunetra Kaviraj (International Journal Of Community Medicine And Public Health, 2025)
Background: Menopausal health demands priority in Indian scenario due to increase in life expectancy and growing population of menopausal women. There is considerably lack of awareness about the effects of the menopausal symptoms in women in India. This study was done to find out the sociodemographic and behavioural characteristics of the study population, to assess Quality of Life (QOL) of the study population by Menopause-Specific Quality of Life Questionnaire (MENQOL) and to elicit the association between menopausal symptoms and sociodemographic and behavioural characteristics of the respondents. Methods: It was a cross-sectional community based observational study conducted from 1st July-31st August 2024 in a rural area of West Bengal among 120 postmenopausal women. Data was obtained using a structured questionnaire and was analysed using SPSS version 21.0. Results: Out of 120 postmenopausal women; vasomotor symptoms seen: hot flushes-67.5%, psychosocial symptoms: anxiety and nervousness-36.7% cases, physical symptoms: feeling tired and difficulty in sleeping-39.2%, sexual changes: 27.5%-avoiding intimacy. Tests of association revealed statistically significant association between: Vasomotor symptoms of study participants and their age, education, type of house. Psychological symptoms and age of the participants. Physical symptoms and education of the participants. No significant association was found between sexual symptoms and socio-demographic characteristics of the study subjects. Conclusions: The results show that menopause causes both physical and psychiatric problems. A large number of women in the world suffer from menopausal symptoms and the problem cannot be ignored.